Transforming mental well‐being for people with diabetes: research recommendations from Diabetes UK's 2019 Diabetes and Mental Well‐Being Workshop - Wylie, TAF; Shah, C; Connor, R; Farmer, AJ; Ismail, K; Millar, B; Morris, A; Reynolds, RM; Robertson, E; Swindell, R; Warren, E; Holt, RIG (Wiley, 2019)
Aims To identify key gaps in the research evidence base that could help to improve the mental well‐being of people with diabetes, and to provide recommendations to researchers and research funders on how best to address them.